Vortioxetine‐induced syndrome of inappropriate secretion of antidiuretic hormone: A case report - Taro Sasaki; Yunosuke Shindo; Kota Kikuchi; Yasushi Kawamata; Norio Sugawara; Norio Yasui‐Furukori (Wiley, 2024)
Abstract Background Vortioxetine, known for its efficacy in treating depression through its effects on various neurotransmitters, has not been previously reported to induce syndrome of inappropriate secretion of antidiuretic hormone (SIADH). Case Presentation This case report describes a 74‐year‐old man with major depressive disorder who developed SIADH 1 week after starting treatment with vortioxetine. SIADH is characterized by symptoms such as headache, nausea, disorientation, and seizures, stemming from hyponatremia (123 mEq/L), without dehydration or edema. Vortioxetine was discontinued, and an alternative drug, mianserin, was initiated. The patient was restricted from drinking water due to hyponatremia. The serum Na concentration improved over time to within the normal range by the second week after admission. Conclusion This is the first case report of vortioxetine‐induced SIADH.